ANALISIS FAKTOR YANG MEMPENGARUHI KEPUTUSAN NASABAH MUSLIM MEMILIH BANK KONVENSIONAL DIBANDING BANK SYARIAH (STUDI KASUS MAHASISWA UPI) - Agistia Nurbani Rajaba; Fitriyani Dwi Azzahra; Keisha Azzahra Fauzita; Wini Anisa Apriliani; Ardhan Mardiant; Edi Suresman (Cahaya Ilmu Bangsa, 2025)
This study aims to analyze the factors influencing Muslim students' decisions in choosing between Islamic banks and conventional banks. Although most respondents understand the differences between the two banking systems, they still prefer conventional banks. Previous research suggests that ease of access and advanced service features are the primary factors in bank selection. This study employs a quantitative approach using surveys targeting Muslim students as primary respondents. The findings reveal that the main factors influencing banking preferences include accessibility, service reach, advanced digital features, and attractive promotional programs. Additionally, long-standing habits of using conventional banks and environmental influences play a significant role in customers' decisions. Meanwhile, students who choose Islamic banks are primarily driven by religious awareness and the desire to avoid riba. This study provides insights into the challenges faced by Islamic banking and the need for enhanced digital services and more innovative marketing strategies to compete with conventional banks.